Effect of Remote and Local Acupuncture Points on Periarthritis of Shoulder: A Comparative Study - Kumaresan Poorna Chandran; Prabu Poorna Chandran; Naveena Arumugam; Sendhilkumar Muthappan (Medical Association of Pharmacopuncture Institute, 2021)
Background : Periarthritis of shoulder is a painful condition of the shoulder, affecting 2-3% of the general population and 20% of diabetic patients. Acupuncture is a widely practiced traditional Chinese medicine. Recent evidence shows that it alleviates shoulder pain with different needling techniques. Objectives: The present study is to compare the efficacy of remote and local points on PAS. Methods : 60 subjects were randomly assigned into two groups, remote acupuncture group (n = 30) and local acupuncture group (n = 30). Both groups were assessed at baseline and at the end of 12 sessions. Shoulder pain and its disability index (SPADI) and (ROM) were measured using goniometer. The intervention was given weekly thrice on alternate days for four weeks with 20 min for each session. Results : The result shows that both remote and local acupuncture points were beneficial in the pain management and rage of motion when compared within the group. The effects of acupuncture at remote acupoints were better than those at local acupoints in SPADI and ROM when compared between two groups. Conclusion : In treatment of periarthritis of shoulder remote acupuncture points may have higher therapeutic value when compared to local points.